The added value of cardiac index and pulse pressure variation monitoring to mean arterial pressure‐guided volume therapy in moderate‐risk abdominal surgery (COGUIDE): a pragmatic multicentre randomised controlled trial. (25th May 2017) - Stens, J.; Hering, J.‐P.; van der Hoeven, C. W. P.; Boom, A.; Traast, H. S.; Garmers, L. E.; Loer, S. A.; Boer, C.
Summary: There is disagreement regarding the benefits of goal‐directed therapy in moderate‐risk abdominal surgery. Therefore, we tested the hypothesis that the addition of non‐invasive cardiac index and pulse pressure variation monitoring to mean arterial pressure‐based goal‐directed therapy would reduce the incidence of postoperative complications in patients having moderate‐risk abdominal surgery. In this pragmatic multicentre randomised controlled trial, we randomly allocated 244 patients by envelope drawing in a 1:1 fashion, stratified per centre. All patients had mean arterial pressure, cardiac index and pulse pressure variation measured continuously. In one group, healthcare professionals were blinded to cardiac index and pulse pressure variation values and were asked to guide haemodynamic therapy only based on mean arterial pressure (control group). In the second group, cardiac index and pulse pressure variation values were displayed and kept within target ranges following a pre‐defined algorithm (CI‐PPV group). The primary endpoint was the incidence of postoperative complications within 30 days. One hundred and seventy‐five patients were eligible for final analysis. Overall complication rates were similar (42/94 (44.7%) vs. 38/81 (46.9%) in the control and CI‐PPV groups, respectively; p = 0.95). The CI‐PPV group had lower mean (SD) pulse pressure variation values (9.5 (2.0)% vs. 11.9 (4.6)%; p = 0.003) and higher mean (SD) cardiac indices (2.76 (0.62) l min −1 .m −2 vs. 2.53 (0.66) l min −1 .m −2 ; p = 0.004) than the control group. In moderate‐risk abdominal surgery, we observed no additional value of cardiac index and pulse pressure variation‐guided haemodynamic therapy to mean arterial pressure‐guided volume therapy with regard to postoperative complications.